Research progress on and molecular mechanism of vacuum sealing drainage in the treatment of diabetic foot ulcers - Lu, Yongpan; Zhao, Dejie; Cao, Guoqi; Yin, Siyuan; Liu, Chunyan; Song, Ru; Ma, Jiaxu; Sun, Rui; Wu, Zhenjie; Liu, Jian; Wu, Peng; Wang, Yibing (Frontiers in Surgery, 2024)
Diabetic foot ulcers (DFUs) are common chronic wounds and a common complication of diabetes. The foot is the main site of diabetic ulcers, which involve small and medium-sized arteries, peripheral nerves, and microcirculation, among others. DFUs are prone to coinfections and affect many diabetic patients. In recent years, interdisciplinary research combining medicine and material science has been increasing and has achieved significant clinical therapeutic effects, and the application of vacuum sealing drainage (VSD) in the treatment of DFUs is a typical representative of this progress, but the mechanism of action remains unclear. In this review, we integrated bioinformatics and literature and found that ferroptosis is an important signaling pathway through which VSD promotes the healing of DFUs and that System Xc-GSH-GPX4 and NAD(P)H-CoQ10-FSP1 are important axes in this signaling pathway, and we speculate that VSD is most likely to inhibit ferroptosis to promote DFU healing through the above axes. In addition, we found that some classical pathways, such as the TNF, NF-κB, and Wnt/β-catenin pathways, are also involved in the VSD-mediated promotion of DFU healing. We also compiled and reviewed the progress from clinical studies on VSD, and this information provides a reference for the study of VSD in the treatment of DFUs.